Sistem Pendukung Keputusan Dalam Rekomendasi Kelayakan nasabah Penerima Kredit Menerapkan Metode MOORA dan MOOSRA - Kusmanto, Kusmanto; Nasution, Mhd Bobbi Kurniawan; Suryadi, Sudi; Karim, Abdul (Building of Informatics, Technology and Science (BITS), 2022)
In selecting credit recipients, it is necessary to have a recipient selection system that can overcome the problem of bad credit that often occurs (loans that are not repaid by the debtor). Based on this problem, a decision support system is needed that helps identify the wrong recipient. The method used in this study is the Moora method and the Moosra method, namely the method for determining priorities. A decision support system is a computer-based system consisting of interacting components: a language system component, a knowledge system component, and a problem-handling system component, and uses data and decision-making models to create semi-structured problems. It solves structured problems and semi-structured problems. and assist in decision making. Structured and unstructured problems, this system helps you get information about your customers, the results are more accurate and on target